EFFECTS OF ADDING BRACKET JOINT ON THE RIGIDITY AND STRENGTH OF BUS T-JOINT STRUCTURE - DENG TengShu; CHEN MingNian (Jixie qiangdu)
T-joint structure is one of the bus basic structures. This paper discussed the effects of triangle bracket size and four forms of triangle brackets（ double brackets added at vertical rod single side,double brackets added at vertical rod both sides,single bracket added at vertical rod both sides,single bracket added at vertical rod crossing symmetric sides） on the rigidity and strength of bus T-joint structure. The calculation by finite element method and experimental analysis showed that: 1Only double brackets added at vertical rod both sides in the four forms of triangle bracket can evidently increase both the rigidity and strength of bus T-joint,2Under the bending loads two forms can be selected compatibly for T-joint structure,3Under the torsion loads double brackets added at vertical rod both sides should be selected for T-joint structure. This research findings can be referred for joint structure design of bus body.